Molecular mechanism of tualang honey on 12% cholesterol diet induced nonalcoholic steatohepatitis (NASH) animal model - Abdul Rahim, Roslina; Muhammad, Naznin; Abdullah, Nor Zamzila (2018)
This study aimed to examine the effects of tualang honey against the high cholesterol diet induced biochemical and histological changes in the kidney, liver and pancreas. Methods: Female Sprague-Dawley rats were used where the control group (n = 5) was fed with commercial rat pellet; the high cholesterol diet (HCD) group (n= 5) was given 12% cholesterol diet; while the HCD with tualang honey (HCD+TH) group (n =5) was fed with 12% cholesterol diet with daily 1.4 g/kg/day of tualang honey. Biochemical analyses for lipid profile and renal function test were performed at completed 48 hours, 7 days, and 6 weeks. The rats were sacrificed at completed 6 weeks and the kidneys were harvested and subjected to histopathological examination. Blood biochemical analysis were also analysed at 1 week and 6 weeks for liver function test, fasting insulin, fasting glucose and HOMA-IR. The liver and pancreas tissues were harvested at the end of 6 weeks for histological examination. Results: The cholesterol diet induction resulted in dyslipidaemia and abnormal liver function. The HCD+TH group have shown an increase in total cholesterol, LDL-c, ALP levels and decreased TG, HDL-c and AST levels significantly at the end of 6 weeks compared to HCD group. Consumption of 12% cholesterol diet for six weeks resulted in an increment of the mean serum creatinine level of the HCD and HCD+TH groups to 1.5 times the control level at the completed 7 days. Also overall both the mean serum creatinine and blood urea levels were higher in HCD group than the control group. With tualang honey supplementation, the mean serum creatinine level showed significant reduction at 48 hours in the HCD+TH group as compared to the HCD group. There was also a reduction in the mean serum creatinine level at the completed 6 weeks. . Histopathologically the kidneys exhibited segmental mesangial hypercellularity and mesangial matrix expansion of almost all the glomeruli in both HCD and HCD+TH groups. The mean plasma glucose level was elevated at 1 week in the HCD group. Plasma insulin levels were higher in HCD+TH group at both 1 and 6 weeks. The HOMA-IR was also higher at 1 week in the HCD+TH group. The liver histology of both HCD and HCD+TH groups showed steatohepatitis with minimal hepatocyte degeneration while the pancreatic sections revealed no abnormalities. Conclusion: The 12% cholesterol diet of 6 weeks duration in this study did induce some features of NASH with dyslipidaemia with abnormal liver profile and also acute kidney injury. The tualang honey exerts some degree of renoprotective effect against high cholesterol diet induced kidney injury, but exhibited no effect on dyslipidaemia and histopathological changes in liver and pancreas.